Aplikasi Game Strategi Menggunakan Metode Algoritma Genetika untuk Pembuatan Pasukan - Pranata, Johan; Purba, Kristo Radion; Liliana, Liliana (Jurnal Infra, 2016)
One way that can be used to provide education in an interesting way is using game. A kind of gameâs genre that can be used to provide entertainment and educational to the player is a turn-based strategy game. As a turn-based strategy game, Battle of Batavia requires AI as opponent which can take good decision for making and controlling units to make the game become more attractive.To create AI that can think well, an AI system that can think properly in game is created. The system uses genetic algorithm method to take decision in making and controlling units. In this thesis, there are 2 component created for this thesis, the first is the genetic algorithm system and the second is Battle of Batavia game.The results show that the genetic algorithm system can be developed so the AI can think much better by determining fitness criteria that affect on taking decision in making and controlling units. The results also show that the genetic algorithm system can make a better decision than random method on some in-game conditions.